Freeway geometric design for active traffic management in Europe - Jones, Jeffrey C. (Office of International Programs, FHWA/US DOT (HPIP), 2011)
A scanning study of England, Germany, the Netherlands, and Spain to examine the use of innovative geometric design practices and techniques to improve the operational performance of congested freeway facilities without compromising safety. Managed motorways are a combination of active or dynamically managed operational regimes, specific designs of infrastructure, and technology solutions. The concept uses a range of traffic management measures to actively monitor the motorway and dynamically control speeds, add capacity, and inform road users of conditions on the network with the objective to optimize traffic and safety performance.
Title from PDF title page (viewed on January 28, 2010).
"March 2011."
"Performing organization, American Trade Initiatives"--Technical report documentation page.
"FHWA-PL-11-004."
"HPIP/3-11(3.5)EW."
Keywords: Traffic engineering -- European Union countries.; Managed lanes (Traffic engineering) -- European Union countries.; Express highways -- European Union countries -- Management.; Europe -- European Union countries.; elektronické knihy; electronic books